Seasonal analysis (six-months) of blood parameters of Kyrgyz elite athletics athletes before 2016 Rio Olympic Games - Kisadere, I.; Patlar, S.; Dzhanuzakov, K.; Kilic, M.; Günay, M.; KhmanovaP.; Güzelbektes, H.; GerI, S.; Demirhan, B. (Acta Medica Mediterranea, 2021)
Objective: In this study, exercise-induced changes in blood parameters of Kyrgyz elite athletes were evaluated during 6 months. Methods: Eight male (n = 8) and three female (n = 3) athletes were included. Blood samples were taken at 3 months intervals before and after the exercise (shuttle run). Erythrocyte (RBC), total leukocyte (WBC), platelet (PLT), neutrophil (NOTR), lymphocyte (LNF) count, hemoglobin (HGB) and hematocrit (HCT) values, mean erythrocyte volume (MCV), mean erythrocyte hemoglobin concentration (MCHC) and also venous blood pH, PO2, PCO2, SAT O2, HCO3, BE, Na, K, Cl, serum glucose (Glu), total protein (TP), total cholesterol (TC), HDL cholesterol (HDL-C), triglyceride (Trig), blood urea nitrogen (BUN), creatinine (Creat), lactate dehydrogenase (LDH) and creatinine phosphokinase (CPK) levels were determined. Results: The WBC, LNF, and NOTR values of the male athletes were found high (p < 0.05) after the exercise periods. In male athletes, HDL-C and BUN levels increased (p < 0.05), while Glu levels (p < 0.05) decreased due to exercise in each measurement. An increased pO2, O2SAT, K, and Anion Gap levels, however, decreased pH, pCO2, HCO3, and BE values were determined after the exercise. Conclusion: Our data showed that exercise caused an acute increase in immune system cell counts (WBC, LNF and NOTR), also HDL-C and O2SAT values in male elite athletics athletes, but the six-month period did not cause any significant change in all of the blood parameters.